2021
DOI: 10.1021/acssensors.1c00063
|View full text |Cite
|
Sign up to set email alerts
|

SERS-Microfluidic Approach for the Quantitative Detection of miRNA Using DNAzyme-Mediated Reciprocal Signal Amplification

Abstract: MicroRNAs (miRNAs) play important roles in biological processes. Designing a sensitive, selective, and rapid method of miRNA detection is crucial for biological research. Here, with a reciprocal signal amplification (RSA) probe, this work established a novel surface-enhanced Raman scattering (SERS)-microfluidic approach for the quantitative analysis of miRNA. First, via a DNAzyme self-assemble cycle reaction, two types of SERS signals produce amplified reciprocal changes. The sum of the absolute signal value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Nucleic acid engineering can produce many cyclic products from a single target by rationally-designed nucleic acid sequences. Based on this concept, nuclease-assisted amplification methods have been adopted to fabricate miRNAs assays 94 , 95 . Briefly, DNA in the hybrid duplex chain of DNA and miRNA will hydrolyze in the presence of exonuclease or duplex-specific nuclease.…”
Section: Introductionmentioning
confidence: 99%
“…Nucleic acid engineering can produce many cyclic products from a single target by rationally-designed nucleic acid sequences. Based on this concept, nuclease-assisted amplification methods have been adopted to fabricate miRNAs assays 94 , 95 . Briefly, DNA in the hybrid duplex chain of DNA and miRNA will hydrolyze in the presence of exonuclease or duplex-specific nuclease.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a sort of small noncoding and single-stranded RNA with the length of 18–25 nucleotides, which play critical roles in the regulation of gene expression at the translation level. Many reported studies have shown that the abnormal or mutation expression of certain miRNAs is connected with the pathogenesis of some cancers, making them a valuable biomarker for early diagnosis of various cancers including lung, breast, colorectal, prostate, and so forth. For instance, in a perspective view, miRNA-21 was reported to have overexpression in various cancer cell lines and was regarded to be closely related to the chemotherapeutic sensitivity of tumors. Thus, the development of analytical technologies that can accurately detect miRNA expression levels is very important for the early disease diagnosis and the monitoring of the therapeutic effect. ,, However, the highly efficient analysis of miRNAs is especially challenging due to their short length, facile degradation, low cellular abundance, and high sequence homology. , In the last several years, many efforts have been made to build biosensing platforms for miRNA assay, for example, fluorescence, , colorimetry, , electrochemiluminescence, surface-enhanced Raman spectroscopy, , electrochemical , and photoelectrochemical (PEC) , methods, and so forth. Among these platforms, the PEC biosensor has attracted widespread attention due to its advantages of low background signal, excellent sensitivity and stability, especially the advantage of both optical and electrochemical methods by combining photoexcitation and electrochemical detection.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the analytical sensitivity in the quantification of miRNAs, signal amplification technologies have been introduced, such as rolling circle amplification (RCA), , exonuclease assisted amplification, , catalytic hairpin self-assembly (CHA), hybrid chain reaction (HCR), , strand displacement reaction (SDR), , and deoxyribozyme (DNAzyme). , Multicomponent nucleic acid enzymes (MNAzyme) are derived from DNAzyme with higher selectivity and more flexible design . MNAzyme distributes the catalytic core into two partial enzymes (partzyme A and partzyme B), which are composed of a partial catalytic core, a substrate arm and a sensor arm.…”
Section: Introductionmentioning
confidence: 99%